2019
DOI: 10.1111/bcpt.13264
|View full text |Cite
|
Sign up to set email alerts
|

Mercury exposure and its effects on fertility and pregnancy outcome

Abstract: Mercury (Hg), a highly toxic environmental pollutant, shows harmfulness which still represents a big concern for human health, including hazards to fertility and pregnancy outcome. Research has shown that Hg could induce impairments in the reproductive function, cellular deformation of the Leydig cells and the seminiferous tubules, and testicular degeneration as well as abnormal menstrual cycles. Some studies investigated spontaneous abortion and complicated fertility outcome due to occupational Hg exposure. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 150 publications
2
32
0
14
Order By: Relevance
“…Cadmium and lead are two of metals for which inhalation is a significant exposure route. Other metals such as mercury may also effect fertility in women [127]; however, not as much research has focused on this metal. In humans, reduced sperm motility was associated with concentrations of Cd and Pb lower than the highest concentrations found in men with occupational and environmental exposure, respectively [83].…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium and lead are two of metals for which inhalation is a significant exposure route. Other metals such as mercury may also effect fertility in women [127]; however, not as much research has focused on this metal. In humans, reduced sperm motility was associated with concentrations of Cd and Pb lower than the highest concentrations found in men with occupational and environmental exposure, respectively [83].…”
Section: Discussionmentioning
confidence: 99%
“…Khan et al (), who gave mercuric chloride (HgCl 2 ) orally to mice, reported that mercury caused a decrease in reproductive performance. Mercuric chloride reduces reproductive performance by causing cellular deformation and testicular degeneration in Leydig cells and seminiferous tubules (Bjorklund et al, ; Chowdhury & Arora, ). Mercury is a proxidant that causes oxidative stress (El‐Desoky et al, ; Ibrahim et al, ; Khan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Organiczne i nieorganiczne związki rtęci mogą kumulo wać się w gruczołach endokrynnych: podwzgórzu, przy sadce mózgowej, nadnerczach, jądrach, jajnikach oraz tar czycy [33]. W populacji mężczyzn wśród skutków zdrowotnych nara żenia na ten pierwiastek najczęściej wymienia się impotencję oraz zmniejszenie liczby, obniżenie ruchliwości oraz niepra widłową morfologię plemników w ejakulacie, co stanowi bezpośrednią przyczynę zaburzeń płodności [18,34,35]. Zaburzenia te mogą być skutkiem wpływu rtęci na proces nekrozy oraz zaburzenie funkcji spermatocytów [18].…”
Section: Rtęćunclassified